Development & growth economics - Rahman, M. Akhlaqur, 1926-1992 (Dhaka: Samhati Prokashan, 2015)
Critical essays on economic development between 1955 and 1987; with special reference to Bangladesh.
Includes bibliographical references (pages 290-299).
Rasal
Keywords: Economic development -- Bangladesh; Bangladesh -- Economic policy; Bangladesh -- Economic conditions